Hospital‐acquired conditions in head and neck cancer surgery. (3rd June 2013) - Kochhar, Amit; Pronovost, Peter J.; Gourin, Christine G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The Centers for Medicare and Medicaid Services has identified 10 hospital‐acquired conditions (HACs) for which they will not reimburse care. We sought to determine the incidence of HACs in head and neck cancer (HNCA) surgery and the association with in‐hospital mortality, complications, length of hospitalization, and costs. Study Design Retrospective cross‐sectional study. Methods Discharge data from the Nationwide Inpatient Sample for 123, 662 patients who underwent an ablative procedure for a malignant oral cavity, laryngeal, hypopharyngeal, or oropharyngeal neoplasm during 2001–2008 were analyzed using cross‐tabulations and multivariate regression modeling. Results HACs occurred in <1% of cases, with vascular catheter‐associated infection comprising >70% of all HACs. The occurrence of HACs was significantly associated with urgent or emergent admission (odds ratio [OR]=2.0, P=.004), major surgical procedures (OR=2.3, P<.001), flap reconstruction (OR=3.5, P<.001), and advanced comorbidity (OR=2.0, P<.001). There was no association between HACs and hospital size, location, ownership, volume status, or safety‐net burden. HACs were significantly associated with in‐hospital mortality (OR=3.8, P=.001), surgical complications (OR=4.9, P<.001), and medical complications (OR=5.6, P<.001). After controlling for all other variables, HACs were associated with significantly increased length of hospitalization and hospital‐related costs, with vascular catheter‐associated infection and foreign object after surgery associated with the greatest increase in length of stay and costs. Conclusions HACs are uncommon events in HNCA surgical patients. Because prediction of HACs is poor and the potential for human error crosses demographic, geographic, and structural boundaries, universal innovative measures to reduce the occurrence of HACs are needed. Level of Evidence 2c. Laryngoscope, 2013